Earthquake risk mitigation in Istanbul museums - Erdik, Mustafa; Durukal, Eser; Erturk, Nevra; Sungay, Bilgen (SPRINGER, 2010)
Considering the number of endangered museums in Istanbul and the size of their collections, assessing and mitigating the earthquake risk is an immense task by any standard. This paper provides a status report on the current earthquake risk mitigation efforts taken by the museums in Turkey. It summarizes several projects that have been carried out over the past few years to protect museums and its collections from earthquake damage and defines future actions that would mitigate earthquake risks associated with museum buildings and their contents.
Keywords: Earthquake; Museums; Istanbul; Risk; Mitigation; Geology; Meteorology & Atmospheric Sciences; Water Resources